2018
DOI: 10.1089/jayao.2018.0048
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Hope and Risk Among Adolescent and Young Adult Cancer Patients with Late-Stage Cancer: A Qualitative Interview Study

Abstract: AYA patients and clinicians provided insights into the experiences and decision-making processes of AYA patients choosing to continue or discontinue treatment and into the areas for improvement in patient-centered oncology care. Taken together, these data provide important suggestions for clinicians caring for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Hope in cancer patients was reported by 60 (21.7%) articles. One study identified three main objects of hope for patients with cancer 68 : breakthrough treatments, cures, 69 , 70 and future children or family. 71–74 Hope was shown to predict resilience, 75 , 76 mitigate future distress, 77 and aid recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Hope in cancer patients was reported by 60 (21.7%) articles. One study identified three main objects of hope for patients with cancer 68 : breakthrough treatments, cures, 69 , 70 and future children or family. 71–74 Hope was shown to predict resilience, 75 , 76 mitigate future distress, 77 and aid recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of control over their life and the psychological challenge of anticipatory grief over the life that has not yet been lived might be difficult for AYAs to process ( 10 , 11 , 13 ). Due to the prognostic uncertainty, AYAs are constantly balancing between hope and fear amidst uncertain treatment outcomes ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This oscillation in the time of diagnosis suggests realities and understandings that can be different between the participants included in the study. According to a study (15) carried out in the United States, which sought to understand the perspectives of adolescents and young adults diagnosed with advanced cancer, it was seen that over the time of diagnosis and treatment, they became more resilient with regard to the disease condition experienced (15) .…”
Section: Resultsmentioning
confidence: 99%
“…The participants try to believe that everything will work out and that they will overcome the disease. Some individual factors can contribute to resilience in adolescents, such as: temperament, learning power, emotional stability, ability to control anger, overcome frustrations quickly, positive self-image, confidence, optimism and positive thinking, ability to solve problems, make decisions, resolve conflicts and manage stress, in addition to good social skills, such as assertiveness, showing concern, empathy, and humor (15) .…”
Section: Overcoming the Difficult Phase Of The Diseasementioning
confidence: 99%